(untitled) (Third Sector Social Economic Review, 2025)
This study aims to determine the effect of firm-specific factors on the capital structure decisions of the firms in the BIST Metal Goods, Machinery index and to determine the capital structure preference of the firms in this index. For this purpose, the data of 28 firms operating continuously in the BIST Metal Goods, Machinery index between the periods 20015Q1-2024Q4 were analysed. In the study where panel data analysis method is used, total debt ratio, short and long-term debt ratio are taken as dependent variables to determine the capital structure, and firm size, non-debt tax shield, liquidity, tangible fixed assets, growth rate and profitability, which are considered to affect the capital structure, are taken as independent variables. According to the results of the Driscoll Kraay robust estimator, it is found that the assumptions of the Financial Hierarchy theory are valid for all variables except firm size for total debt ratio and short-term debt ratio. When looking at the relationships between the long-term debt ratio and the independent variables, mixed results were obtained in terms of capital structure theories.